AVALIAÇÃO SUBJETIVA GLOBAL PRODUZIDA PELO PACIENTE E SOBREVIVÊNCIA: estudo em hospital de referência em câncer de São Luís (MA) - Santos, Alexsandro Fereira dos (2015)
Introduction: In Brazil, the prevalence of malnutrition in hospitalized patients with cancer is 45.1%, the injury is associated with negative outcomes. Few studies have investigated the association of Subjective Global Assessment Produced by the patient (ASGPPP) as indicator of mortality, and none could match them. Objective: To analyze the association between the score of ASGPPP and mortality in cancer patients in a referral hospital in Sao Luis - MA. Methods: A cross-sectional study with 366 records of cancer patients. We included patients aged 20 or more, hospitalization longer than two days, application ASGPPP between January 2010 to January 2014 was collected age, sex, origin, primary site of disease, metastasis and cancer treatment, time hospitalization, time to implement ASGPPP, outcome (discharge or death), score ASGPPP, weight loss in 1 (PP1%) and 6 (PP6%) months, body mass index (BMI) and weight. Were applied the chi-square test, Student t / Man-Witney, adjusted logistic regression and not adjusted. Results: prevailed women (51.6%) over 59 years (45.1%), coming from St. Louis (48%) with tumors located in the digestive tract (27.6%) without metastases (88.5% ). The surgery was the most prevalent cancer treatment (27.9%) and hospital discharge (78.1%), the deaths accounted for 21.9%. At least 36.1% of the individuals had some degree of malnutrition. Prevailed the time of application of ASGPPP within ten days (72.7%) and the length of stay up to 11 days (47.8%). The application time of ASGPPP correlated directly and positively with duration of hospital stay, the ASGPPP score and PP1% and PP6%. BMI correlated inversely to instrument the application time. After adjusted logistic regression, the presence of malnutrition remained associated with mortality. Malnutrition was associated with an increase in length of stay frequencies exceeding five days and the ASGPPP application time within five days was associated with a reduction in these same cases. But the length of stay greater than 10 days, also inversely associated with implementation of ASGPPP within five days (reduction of 91% of cases). Conclusion: More than half of the patients were not malnourished. Malnutrition by ASGPPP was associated with a longer hospital stay and mortality. The delay in implementing the ASGPPP is a risk marker for the increase in ASGPPP score, length of hospital stay and mortality. Measures aimed at shortening the ASGPPP the time of application should be taken.